Crucial Habitats for the Spangled Ebony Langur: The Role of Former Production Forests in Alas Purwo National Park - Maulahila, Haikal Idris; Rianti, Puji; Rahman, Dede Aulia (Bogor Agricultural University, Indonesia, 2025)
Land use conversion into production forests has led to habitat degradation for primates. On the other hand, most primates have started adapting to the presence of these habitats and have forced conservation efforts to focus on the production forests. Our study at the Kucur Resort, Alas Purwo National Park, reported the population estimates using distance sampling, composition and diversity of vegetation, and habitat suitability of Trachypithecus auratus using multi-algorithm approach in former production forests consisting of jungle and rehabilitation zones. Our study estimated the population density of T. auratus at around 1.29 individuals per km2. We found an association between the number of encounters and the diversity of vegetation in each zone, although it was dominated by Tectona grandis. In addition, we predict that the area of suitable habitat is always smaller than the unsuitable habitat and suggest the model from Boosted Regression Tree as a management reference. We assume that the presence of T. auratus in this habitat is influenced by food availability, distance from settlements, and slope. This study provides reliable information on the potential of reforesting production forests as a habitat for T. auratus and deserve conservation attention.